ANALYSIS OF STRATEGIES TO INCREASE MOTOR VEHICLE TAX REVENUE AT UPTD PEPENDA SAMSAT MEDAN UTARA - Nanda, Rika Widya (Proceeding International Seminar of Islamic Studies, 2024)
The aim of this research is to determine the strategy for increasing Motor Vehicle Tax revenue at the North Medan Samsat UPT, and to determine the inhibiting factors in implementing the strategy for increasing Motor Vehicle Tax revenue at the North Medan Samsat UPT. Researchers used a qualitative descriptive method, namely analysis that provides a detailed picture based on the results of observations, interviews and documentation. The results of the research show that the strategy to increase Motor Vehicle Tax revenue at the North Medan Samsat UPT has been implemented optimally, and the program strategy most widely utilized by taxpayers is tax whitening. The inhibiting factors in implementing the strategy to increase Motor Vehicle Tax revenue are: the economic condition of the community/taxpayers, the level of public awareness which is still very low in making tax payments, and the public's lack of utilization of developments in information technology in paying taxes.